Comparison of Intramedullary Nailing Versus Plate Fixation in Tibial Shaft Fractures: A Clinical Study - ARIF, FIZA (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Tibial shaft fractures are one of the most common long-bone fractures and can lead to substantial morbidity and disability. Operative fixation is the standard of care for the majority of displaced fractures, and two of the most common methods are intramedullary nailing and plate fixation. But the best method of fixation is still controversial. Objective: To compare the clinical and radiological outcomes of intramedullary nailing versus plate fixation in the management of tibial shaft fractures. Methods: This comparative clinical study was performed over a period of one year from March 2024 to March 2025 on 60 adult patients with tibial shaft fractures. The patients were equally divided into two groups: 30 patients were treated with intramedullary interlocking nailing, and 30 with plate fixation. We gathered information on patient demographics, surgical parameters, union time, functional outcome and complications, which were analyzed using SPSS version 26. We used the Johner and Wruhs criteria to evaluate the functional outcome, with a p-value of <0.05 as statistically significant. Results: Intramedullary nailing demonstrated significantly shorter operative time, reduced hospital stay, and earlier weight-bearing compared to plate fixation (p<0.05). Radiological union also occurred earlier in the nailing group (17.2 ± 3.1 weeks) than in the plating group (20.4 ± 3.8 weeks). Intramedullary nailing was associated with a greater rate of excellent to good functional outcome. Superficial infection and irritation were more frequent in the plating group, while anterior knee pain was more frequent in the nailing group. Conclusion: Intramedullary nailing and plate fixation are both effective treatments for tibial shaft fractures, but intramedullary nailing is associated with better outcomes in terms of early weight bearing, time to fracture union, and wound complications. It should be the method of choice when possible.